Community of helminth parasites of thorny toad Rhinella Spinulosa (Anura: Bufonidae) of Peru - Chero, Jhon (2016)
The aim of this study was to evaluate the community of metazoan parasites of thorny toad Rhinella spinulosa of Peru and elucidate whether sex and the total length of the hosts amphibians are structuring their communities of parasites. Ninety specimens of R. spinulosa were acquired during May 2009 to October 2010. The body cavity, gastrointestinal tract, bladder, lungs and muscles were examined to search for metazoan parasites. Seven taxa of metazoan parasites were collected: one digenean [Gorgoderina chilensis (Gorgoderidae) in the bladder] a cestode [Cylindrotaenia aff. americana (Proteocephalidae) in the small intestine], four nematodes [Aplectana hylambatis and A. vellardi (Cosmocercidae) in the large intestine, Hedruris moniezi (Hedruridae) in the stomach and Rhabdias aff. pseudosphaerocephala (Rhabdiasidae) in lungs] and one acanthocephalan [Pseudoacanthocephalus lutzi (Echinorhynchidae) in the small intestine]. A positive correlation was observed between length and mean abundance of R. aff. pseudosphaerocephala, and an association between sex and mean abundance of G. chilensis, A. hylambatis and R. aff. pseudosphaerocephala. G. chilensis showed dependence on the sex of R. spinulosa. The three levels of aggregation (dispersion index, index discrepancy of Poulin and K negative binomial equation) showed a contagious distribution. Most of the values of alpha diversity of parasitic infracommunities were lower than those of the community component.